Framework for Greenhouse Gas Emissions Calculations in the Context of Road Freight Transport for the Automotive Industry - Chocholáč, Jan; Hruška, Roman; Machalík, Stanislav; Sommerauerová, Dana; Šohajek, Petr (My University, 2021)
The topic of greenhouse gas emissions calculations in the context of freight transport is very current. This topic is very interesting for many stakeholders, such as companies, suppliers, employees, customers, residents, etc. The automotive industry is a major producer of greenhouse gas emissions from logistic processes. Due to this fact, it is necessary to search for and create frameworks for the calculation of greenhouse gas emissions in this sector. The requirements for the calculation of greenhouse gas emissions from road freight transport in the automotive industry were identified using semi-structured interviews. Available emission freight calculators were analyzed using the content and comparative analysis. The proposed frameworks for greenhouse gas emissions calculations in the context of road freight transport of material and finished manufactured passenger cars for the automotive industry were applied in the form of an interpretative case study. The main result of the article is the proposal of the frameworks for greenhouse gas (carbon and sulfur dioxide) emissions calculations in the context of road freight transport of the material and finished manufactured passenger cars for the automotive industry. The proposed frameworks were applied and verified. The use of the proposed frameworks can be expected in logistic planning and decision-making.
Rámec pro kalkulace emisí skleníkových plynů v kontextu silniční nákladní dopravy pro automobilový průmysl
Keywords: logistics; transportation; road freight transport; greenhouse gas emissions; greenhouse gas emissions calculator; automotive industry; logistika; doprava; silniční nákladní doprava; emise skleníkových plynů; kalkulačka emisí skleníkových plynů; automobilový průmysl